Active carpets drive non-equilibrium diffusion and enhanced molecular fluxes - Francisca Guzmán-Lastra (Nature Portfolio, 2021)
Fick’s laws describe the essential physics of diffusion, but it is challenging to extend them to systems out of equilibrium. The authors derive the diffusivity of particles near active carpets - a surface covered with hydrodynamic actuators, which provides a framework for transport in living matter.